Load testing and load balancing for Alumni web application using JMeter - Azizi, Fadhila; Gourine, Khadidja Narimane; Hamini, Nardjes (Laghouat : Université Amar Telidji - Département d'informatique, 2023)
This thesis highlights the development of the alumni web application for the university of laghouat using Angular and MySQL as development tools. The main goal of the alumni website is to provide graduates with a platform to communicate, support each other, and access various services, including alumni profles, event pages, and a job board. To test and ensure the high performance of the alumni application in eﬀectively serving the alumni community and handling diﬀerent user loads, we used Apache JMeter, a tool for load testing. This allowed us to evaluate the application’s performance under various load scenarios that closely resemble real-world usage patterns. Performance was measured based on parameters such as response time, throughput, and error rate. The results of the load testing in normal load scenarios were satisfactory, as the system performed reliably without errors or failures. However, the results of the load testing in high load scenarios were unsatisfactory. The application was unable to handle the sudden load spike, resulting in increased response times, error rates, and degraded performance of the application. To address these issues, load balancing was employed to improve the overall performance, availability, and reliability of the alumni application. This involved distributing network trafc among servers using the Apache JMeter simulator.